Probe Suppression in Conformal Phased Array - Singh, Hema.; Dutta, Mausumi; Neethu, P. S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book considers a cylindrical phased array with microstrip patch antenna elements and half-wavelength dipole antenna elements. The effect of platform and mutual coupling effect is included in the analysis. The non-planar geometry is tackled by using Euler's transformation towards the calculation of array manifold. Results are presented for both conducting and dielectric cylinder. The optimal weights obtained are used to generate adapted pattern according to a given signal scenario. It is shown that array along with adaptive algorithm is able to cater to an arbitrary signal environment even when the platform effect and mutual coupling is taken into account. This book provides a step-by-step approach for analyzing the probe suppression in non-planar geometry. Its detailed illustrations and analysis will be a useful text for graduate and research students, scientists and engineers working in the area of phased arrays, low-observables and stealth technology.
Introduction -- Steering Vector of Conformal Phased Array -- Optimal Antenna Excitations and Adapted Pattern -- Probe Suppression in Spatially Arranged Phased Array -- Probe Suppression in Dipole Phased Array Mounted on a Right Circular Cylinder -- Conclusion -- References -- Subject Index.
Keywords: Telecommunication; Electrodynamics; Electronics; Microwaves, RF Engineering and Optical Communications; Classical Electrodynamics; Electronics and Microelectronics, Instrumentation